Experimental investigation of straight shape thermosyphon filled with R410A refrigerant - Revichandran, Rajeanderan; Mohiuddin, A. K. M.; Uddin, Mohammad Faisal (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The thermal performances of a R410A filled thermosyphon subjected to low heat flux from 1882 W/m2 to 4423 W/m2 and evaporator wall temperatures between 20 °C and 40 °C with fill ratios 0.75 and 1.00 and at different inclinations from 45° to 90° were investigated. The axial temperature distribution of the thermosyphon was found to be uniform for all temperatures difference of evaporator at all power inputs. The performance of the thermosyphon which is determined from the heat transfer capability of the thermosyphon was found to be dependent of inclination angle and fill ratio. Experimental results show that heat transfer coefficient increases as the heat input increase while thermal resistance decreases exponentially with increasing input power. Increase in fill ratio and inclination angle at various heat input contributed to a better thermosyphon performance, at where heat transfer was highest at fill ratio 1.00 and inclination angle of 68°.